Induced resistance by oxidative shifts in pigeonpea (Cajanus cajan L.) following Helicoverpa armigera (Hübner) herbivory. Issue 5 (25th July 2014) - Kaur, Rimaljeet; Gupta, Anil K; Taggar, Gaurav K
Abstract BACKGROUND Oxidative responses in leaves, developing seeds and the pod wall of nine pigeonpea genotypes were investigated against Helicoverpa armigera feeding. Out of nine genotypes, four were moderately resistant, three were intermediate and two were moderately susceptible genotypes. RESULTS A significant shift in the oxidative status of pigeonpea following herbivory was depicted by the upregulation of diamine oxidase (DAO), polyamine oxidase (PAO) and lipoxygenase 2 (LOX 2) activities. Polyphenol oxidase (PPO) activity was significantly higher in the infested pod wall and leaves of moderately resistant genotypes than in those of moderately susceptible genotypes. H. armigera infestation markedly enhanced phenylalanine ammonia lyase (PAL) and tyrosine ammonia lyase (TAL) activities in wounded tissues. The decline in ascorbate peroxidase (APX) activity and ascorbate content was lower in moderately resistant genotypes than in moderately susceptible genotypes. A significant decrease in LOX 3 activity was also observed in the infested pod wall of moderately resistant and intermediate genotypes. A lower malondialdehyde (MDA) content and higher proline content of the infested pod wall and developing seeds was observed. Higher activities of PPO, PAL and proline content in leaves of uninfested moderately resistant genotypes could either be an unrelated observation or alternatively could help in identifying H. armigera‐resistant genotypes. CONCLUSION The increase in activities of PPO, DAO, PAO, PAL and TAL and higher proline and lower MDA content upon herbivory suggested their integrated contribution in providing resistance to pigeonpea against H. armigera. © 2014 Society of Chemical Industry